PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIMEDIA DI STMIK YMI TEGAL - Syefudin (Nusantara Hasana Berdikari, 2022)
This study aims to identify multimedia-based Islamic religious education, and the problems experienced in multimedia-based Islamic religious education at STMIK YMI TEGAL. The type of research used in carrying out this research is a type of qualitative descriptive research. Descriptive research is research that seeks to describe an indication and event. On the other hand, the approach used is qualitative. Qualitative research examines participants' perspectives with interactive and flexible strategies. In collecting information using the procedures for observation, interviews, and documentation. After the information is collected, then the information is analyzed using information reduction analysis, information presentation, and drawing conclusions. The results of this study prove that: 1) Lecturers have implemented multimedia technologies such as video players, photos, power points, and Microsoft Word and use PC/laptop technology and telecommunications technology. 2) Lecturers have carried out the PAI education process in accordance with the RPS and Gagne's educational theory. 3) As many as 88% of students get a positive reaction and during the lesson students are more interested in using multimedia than using the lecture method.